2009
DOI: 10.1094/mpmi-22-3-0235
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Brassica napus MPK4 Enhances Resistance to Sclerotinia sclerotiorum in Oilseed Rape

Abstract: Sclerotinia sclerotiorum causes a highly destructive disease in oilseed rape (Brassica napus) resulting in significant economic losses. Studies on the Arabidopsis thaliana MPK4 loss-of-function mutant have implicated that AtMPK4 is involved in plant defense regulation, and its effect on disease resistance varies in different plant-pathogen interactions. In this study, we isolated a B. napus mitogen-activated protein kinase, BnMPK4, and found that BnMPK4 along with PDF1.2 are inducible in resistant line Zhongsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 46 publications
3
70
0
Order By: Relevance
“…Expression of the WRKY33 gene is highly inducible by B. cinerea infection (AbuQamar et al, 2006), but the induction does not require the JA and ET signaling components COI1 and EIN2, respectively (Zheng et al, 2006), suggesting that WRKY33 may be activated by a JA/ET-independent defense pathway. Recently, Wang et al (2014) reported that expression of the BnWRKY33 gene is highly inducible by S. sclerotiorum infection and that overexpression of BnWRKY33 in B. napus leads to increased basal expression of BnPDF1.2 and resistance to S. sclerotiorum. Consistent with that report, we found that the Arabidopsis wrky33-1 mutant is more susceptible to S. sclerotiorum than the wild type and that overexpression of WRKY33 confers a low level of resistance to S. sclerotiorum during early time points of infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the WRKY33 gene is highly inducible by B. cinerea infection (AbuQamar et al, 2006), but the induction does not require the JA and ET signaling components COI1 and EIN2, respectively (Zheng et al, 2006), suggesting that WRKY33 may be activated by a JA/ET-independent defense pathway. Recently, Wang et al (2014) reported that expression of the BnWRKY33 gene is highly inducible by S. sclerotiorum infection and that overexpression of BnWRKY33 in B. napus leads to increased basal expression of BnPDF1.2 and resistance to S. sclerotiorum. Consistent with that report, we found that the Arabidopsis wrky33-1 mutant is more susceptible to S. sclerotiorum than the wild type and that overexpression of WRKY33 confers a low level of resistance to S. sclerotiorum during early time points of infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic interactions between S. sclerotiorum and its host plants are ill defined, although some host defence and susceptibility components have been identified (Bessire et al 2007;Guo and Stotz 2007;Wang et al 2009). Virulence factors of S. sclerotiorum are also incompletely understood (Hegedus and Rimmer 2005), but oxalic acid has traditionally been known to play a key role in pathogenesis (de Bary 1886; Godoy et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Cascades of the mitogenactivated protein kinase class play pivotal roles during the establishment of resistance to a variety of stresses (Pitzschke et al 2009). A previous study suggested that overexpression of MAPK4 in B. napus could improve pathogen resistance (Wang et al 2009). Spot U5, which was identified as MAPK4 in this study, was upregulated by 2-fold in Group B, although no obvious effects appeared in plants under Group B conditions.…”
Section: Signaling and Regulationmentioning
confidence: 99%